The connection between shared storybook readings, children's imagination, social interactions, affect, prosocial behavior, and social play. Issue 2 (3rd May 2016) - Kohm, Kristen E.; Holmes, Robyn M.; Romeo, Lynn; Koolidge, Louis
ABSTRACT: This study explored the connection between shared storybook readings and children's imagination, social interactions, affect, prosocial behavior, and social play. A secondary goal investigated the relationship between social play and vocabulary learning. Participants were 44 young children (17 boys, 27 girls) attending preschool in the northeastern United States. Ages ranged from 4.1 to 5.6 years. The majority of the children were from Mexican, Central American, Brazilian, and African-American ethnic heritages. We observed children before and after repeated shared storybook readings that incorporated story props over multiple sessions. We recorded children's imaginative ability, social interaction, affective, helping, and social play behaviors using a time sampling approach. Children also completed the Peabody Picture Vocabulary Test –Four (PPVT-IV). We found shared storybook reading experiences connected positively to social, cognitive, and emotional developmental outcomes as well as social play. Pretend play experiences also positively connected with receptive vocabulary. Our findings support existing literature.